Cosmetic Product Segmentation Analysis Using K-Means Clustering at PT Mandom Bekasi - Mona Dewintha Agustine; Adi Muhajirin; Prio Kustanto (Jurnal Kecerdasan Buatan dan Teknologi Informasi, 2026)
PT Mandom Indonesia Tbk manages a wide range of cosmetic products with varying sales levels and inventory turnover rates, creating challenges in inventory management and marketing strategy formulation. This study aims to segment cosmetic products based on sales patterns and inventory turnover using the K-Means Clustering algorithm within a Knowledge Discovery in Databases (KDD) framework. The research stages include data selection, preprocessing, transformation, clustering, and evaluation. The dataset consists of 436 cosmetic products with attributes including sell in, sell out, stock, and expiration date, sourced from PT Mandom's internal sales report for the year 2025. Feature engineering produced two derived variables, the sell out to sell in ratio and the remaining days until expiration, which were normalized using Min-Max Scaling. The optimal number of clusters, determined using the Elbow Method and validated with the Silhouette Score, was three. The K-Means algorithm successfully grouped the products into three segments: Fast Moving (75 products, 17.2%), Medium Moving (299 products, 68.6%), and Slow Moving (62 products, 14.2%). The Fast Moving cluster exhibited the highest sell in, sell out, and sell-through ratio values, while the Slow Moving cluster showed the lowest ratio, indicating a higher risk of stock accumulation. These segmentation results can serve as a data-driven basis for inventory management, distribution planning, and marketing strategy decisions at PT Mandom.